Degradation of Polycyclic Aromatic Hydrocarbons by a Newly Discovered Enteric Bacterium, Leclercia adecarboxylata - Sarma, Priyangshu Manab (American Society for Microbiology, 2004)
A bacterial strain, PS4040, capable of degrading polycyclic aromatic hydrocarbons for use as the sole carbon source was isolated from oily-sludge-contaminated soil. The 16S rRNA gene showed 98.8% homology to that of Leclercia adecarboxylata. Comparative molecular typing with the clinical strain of L. adecarboxylata revealed that there were few comigrating and few distinct amplimers among them.